Human adenovirus infection induces pulmonary inflammatory damage by triggering noncanonical inflammasomes activation and macrophage pyroptosis - Li, Lexi; Fan, Huifeng; Zhou, Jinyu; Xu, Xuehua; Yang, Diyuan; Wu, Minhao; Cao, Can; Lu, Gen (Frontiers in Immunology, 2023)
Introduction Human adenovirus (HAdV) is a common respiratory virus, which can lead to severe pneumonia in children and immunocompromised persons, and canonical inflammasomes are reported to be involved in anti-HAdV defense. However, whether HAdV induced noncanonical inflammasome activation has not been explored. This study aims to explore the broad roles of noncanonical inflammasomes during HAdV infection to investigate the regulatory mechanism of HAdV-induced pulmonary inflammatory damage. Methods We mined available data on GEO database and collected clinical samples from adenovirus pneumonia pediatric patients to investigate the expression of noncanonical inflammasome and its clinical relevance. An in vitro cell model was employed to investigate the roles of noncanonical inflammasomes in macrophages in response to HAdV infection. Results Bioinformatics analysis showed that inflammasome-related genes, including caspase-4 and caspase-5, were enriched in adenovirus pneumonia. Moreover, caspase-4 and caspase-5 expression levels were significantly increased in the cells isolated from peripheral blood and broncho-alveolar lavage fluid (BALF) of pediatric patients with adenovirus pneumonia, and positively correlated with clinical parameters of inflammatory damage. In vitro experiments revealed that HAdV infection promoted caspase-4/5 expression, activation and pyroptosis in differentiated THP-1 (dTHP-1) human macrophages via NF-κB, rather than STING signaling pathway. Interestingly, silencing of caspase-4 and caspase-5 in dTHP-1 cells suppressed HAdV-induced noncanonical inflammasome activation and macrophage pyroptosis, and dramatically decreased the HAdV titer in cell supernatants, by influencing virus release rather than other stages of virus life cycle. Discussion In conclusion, our study demonstrated that HAdV infection induced macrophage pyroptosis by triggering noncanonical inflammasome activation via a NF-kB-dependent manner, which may explore new perspectives on the pathogenesis of HAdV-induced inflammatory damage. And high expression levels of caspase-4 and caspase-5 may be a biomarker for predicting the severity of adenovirus pneumonia.